1992
DOI: 10.1182/blood.v80.4.1090.1090
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplants may cure patients with acute leukemia never achieving remission with chemotherapy

Abstract: About 30% of adults with acute lymphoblastic leukemia (ALL) and 20% to 40% of children and adults with acute myelogenous leukemia (AML) never achieve remission, even with intensive chemotherapy. Most die of resistant leukemia, often within 6 months or less. In this study of 126 patients with resistant ALL or AML, allogeneic bone marrow transplants from HLA-identical siblings produced remissions in 113 of 115 (98%) evaluable patients. The 3-year probability of leukemia-free survival was 21% (95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(51 citation statements)
references
References 5 publications
5
42
1
3
Order By: Relevance
“…The association of advanced leukaemia and the occurrence of severe GVHD has also been reported by Nash et al (1992). Cumulative effects of prior chemotherapy and reduced tolerance of the intensive conditioning regimens used at BMT (Biggs et al, 1992;Bortin et al, 1981;Clift et al, 1987Clift et al, , 1990Clift et al, , 1991Deeg et al, 1991;Nash et al, 1992) may account in part for the severe GVHD seen in patients transplanted for advanced leukaemia.…”
Section: Discussionmentioning
confidence: 89%
“…The association of advanced leukaemia and the occurrence of severe GVHD has also been reported by Nash et al (1992). Cumulative effects of prior chemotherapy and reduced tolerance of the intensive conditioning regimens used at BMT (Biggs et al, 1992;Bortin et al, 1981;Clift et al, 1987Clift et al, , 1990Clift et al, , 1991Deeg et al, 1991;Nash et al, 1992) may account in part for the severe GVHD seen in patients transplanted for advanced leukaemia.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, our sequential approach M. Mohty et al 188 haematologica | 2017; 102(1) 35 The 2-year overall survival rate was 38%, similar to the 42% reported by Schmid et al using the FLAMSA sequential regimen, 12 and superior to the 20-30% reported after standard MAC allogeneic SCT. 8,10,29 Similarly, Middeke et. al.…”
Section: Discussionmentioning
confidence: 93%
“…Few retrospective studies or case series limited to a small subset of highly selected patients receiving a myeloablative allo-HCT have been reported in the literature. [43][44][45] A large CIBMTR study has recently reported a remarkable 3-year OS rate of 42% with matched-sibling myeloablative allo-HCT in a subset of refractory AML patients who had a good performance status, no circulating blasts, a prior CR duration of > 6 months, and no poor-risk cytogenetics. 46 The role of RIC in refractory AML, however, is more controversial.…”
Section: The Role Of Ric Transplantation In Refractory Amlmentioning
confidence: 99%